2017
DOI: 10.1186/s13071-017-2453-5
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase 4 is involved in the reproduction of the platyhelminth parasite Schistosoma japonicum

Abstract: BackgroundSchistosomiasis is one of the most common parasitic diseases affecting millions of humans and animals worldwide. Understanding the signal transduction pathways and the molecular basis of reproductive regulation in schistosomes is critically important for developing new strategies for preventing and treating these infections. Syk kinases regulate the proliferation, differentiation, morphogenesis, and survival of various types of cells and have been identified in invertebrates. Tyrosine kinase 4 (TK4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…So, our results revealed that SjPhb1 is essential for the growth and development of schistosomes. It was reported that PHB is important in embryonic development and is required for the differentiation of somatic and germline cells in the larval gonads of C elegans , highlighting its essential role in regulating fat metabolism and mitochondrial proliferation during aging 27,28,37,57 . The growth and development of schistosomes depends on continuous nutrient acquisition and metabolism from the host environment, 58 and vitellaria is a highly proliferative organ that occupies almost two thirds of the posterior female worm body and contains a lot of lipid droplets in the vitelline cells, 52,59,60 which implied that Sj PHB1 may also perform similar functions in S. japonicum as PHB does in C elegans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, our results revealed that SjPhb1 is essential for the growth and development of schistosomes. It was reported that PHB is important in embryonic development and is required for the differentiation of somatic and germline cells in the larval gonads of C elegans , highlighting its essential role in regulating fat metabolism and mitochondrial proliferation during aging 27,28,37,57 . The growth and development of schistosomes depends on continuous nutrient acquisition and metabolism from the host environment, 58 and vitellaria is a highly proliferative organ that occupies almost two thirds of the posterior female worm body and contains a lot of lipid droplets in the vitelline cells, 52,59,60 which implied that Sj PHB1 may also perform similar functions in S. japonicum as PHB does in C elegans .…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the digested blood products in the intestine of SjPhb1 knockdown female worms were much less than those in the intestine of control female worms with light black or gray in color of the intestine of SjPhb1 knockdown female worms vs dark black in color of the intestine of control female worms ( Figure S3), which suggested potential defects in feeding or utilizing host blood in the SjPhb1 knockdown female worms, and this is also a probable cause for their retarded growth and development during aging. 27,28,37,57 The growth and development of schistosomes depends on continuous nutrient acquisition and metabolism from the host environment, 58 and vitellaria is a highly proliferative organ that occupies almost two thirds of the posterior female worm body and contains a lot of lipid droplets in the vitelline cells, 52,59,60 which implied that SjPHB1 may also perform similar functions in S. japonicum as PHB does in C elegans.…”
mentioning
confidence: 99%
“…Later, it was discovered that the SjTK4 amino acid sequence shows 76.9% identity and 82.7% similarity with SmTK4 sequence, the gene is differentially expressed in all developmental stages of schistosome both in females and males. With the therapy of piceatannol (a Syk kinase-specific inhibitor), many morphological changes were observed in the testes and ovaries of S. japonicum , and the size and number of whole germ cells in both the testis and ovary are smaller and fewer than the control group, suggesting that TK4 may have a significant effect on the production and development of eggs in vitro ( Ding et al., 2017 ). In addition, the application of piceatannol significantly upregulates the expression of genes related to egg-shell production including P14, P48, egg-shell precursor, and FS800, which in agreement with the results in imatinib-treated S. mansoni , further indicating the functional similarity between SjTK4 and SmTK4 ( Buro et al., 2014 ).…”
Section: Tk Family May Play An Important Role In the Survival Of S Japonicummentioning
confidence: 99%
“…Syk kinases, identi ed in invertebrates, regulate the proliferation, differentiation, and survival of various types of cells. Among Syk kinase family, tyrosine kinase 4 (TK4) is a kinase expressed in Schistosoma mansoni and S. japonicum, which plays a pivotal role in the development of the testis and ovaries in S. mansoni and regulates the gametogenesis of S. japonicum [40]. The fact that Src inhibitors can affect the actin cytoskeleton of Entamoeba histolytica and inhibit the entry of Trypanosoma cruzi provides new targets for designing new drugs against protozoa [41][42].…”
Section: Motifsmentioning
confidence: 99%